PERAN MEDIASI PROFITABILITAS: AKTIVITAS TERHADAP NILAI PERUSAHAAN DENGAN LEVERAGE SEBAGAI VARIABEL KONTROL PADA PERUSAHAAN IDX BUMN 20 PERIODE 2018-2021 - Farid, Dzaki Miftah; Akhmadi, Akhmadi (KEUNIS, 2023)
The decline in the value of BUMN 20 companies in the 2018-2021 period is a problem for this study. The research objective examines the effect of ROA in mediating TATO to PBV. DER is used as a control variable. Based on the purposive sampling method, there are 15 samples of the IDX BUMN 20 firms from 2018 to 2021. This work uses panel data regression, the classic assumption test, the hypothesis test, the Sobel test, and the coefficient of determination with the Eviews 12 program. The study's findings show that (1) TATO significantly positively affects ROA, (2) TATO significantly positively affects PBV, (3) ROA positively affects PBV but not significantly, and (4) ROA is ineffective in moderating the relationship between TATO and PBV; (5) DER has an insignificant positive effect on PBV as a control variable.